Facile Generation of Heat Stable Antiviral and Antitoxin Single Domain Antibodies from a Semi-synthetic Llama Library - Goldman, Ellen R. (2006)
Llamas possess a class of unconventional immunoglobulins that have only heavy-chains; unpaired heavy variable domains are responsible for antigen binding. These domains have previously been cloned and expressed as single domain antibodies (sdAbs); they comprise the smallest known antigen binding fragments. SdAbs have been shown to bind antigens at >90°C and to refold after being denatured. To take advantage of the remarkable properties of sdAbs we constructed a large, semi-synthetic llama sdAb library. This library facilitated the rapid selection of binders to an array of biothreat targets. We selected sdAb specific for live vaccinia virus (a smallpox virus surrogate), hen egg lysozyme, cholera toxin, ricin, and staphylococcal enterotoxin B. The selected sdAb possessed high specificity as well as enhanced thermal stability in comparison to conventional IgG and scFv antibodies. We also determined equilibrium dissociation constants as well as demonstrated the use of several anti-toxin sdAbs as effective capture and reporter molecules in sandwich assays on the Luminex instrument. The ability to rapidly select such rugged antibodies will enhance the reliability of immunoassays by extending shelf-life, and the capacity to function in hostile environments.